The complex adoption pathways of digital technology in Australian livestock supply chains systems - Jackson, Elizabeth; Cook, Simon (Commonwealth Scientific and Industrial Research Organization Publishing, 2022)
This paper reviews early experiences, expectations and obstacles concerning the adoption of digital technologies in Australian livestock systems. Using three case studies of publicly-available information on Australia’s red meat industry, we identify the process of digitally enhanced value creation according to four themes: (1) supply chain operability; (2) product quality; (3) animal welfare; and (4) innovation and learning. We find reasons for both optimism and pessimism concerning the adoption of digital agriculture. While digital technology is being offered by various stakeholders to support collaboration within supply chains, it is also being met with scepticism amongst some producers who are not actively engaging with a digital transformation. We identify that the ‘technology fallacy’, which proposes that organisations, people, learning and processes are as important to digital transformation as the technology itself; but while digital technologies enable change, it is the people who determine how quickly it can occur. We argue that – since quality appears to be the major basis on which Australian red meat producers will compete in global markets – the broad adoption of digital technology will prove increasingly essential to future growth and sustainability of this supply chain.